2022
DOI: 10.1111/liv.15158
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle changes during the coronavirus disease 2019 pandemic impact metabolic dysfunction–associated fatty liver disease

Abstract: Background and Aims The coronavirus disease 2019 (COVID‐19) pandemic precipitated lifestyle changes. We aimed to clarify whether COVID‐19–induced lifestyle changes affected the development of metabolic dysfunction–associated fatty liver disease (MAFLD). Methods This retrospective longitudinal study included 973 participants who underwent health check‐ups between 2018 and 2020. We used data from the MedCity21 health examination registry. Participants' clinical characteristics and lifestyle habits were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…During the COVID-19 pandemic, the incidence of newly diagnosed MAFLD increased. Bidirectionally, MAFLD is associated with COVID-19 severity [ 31 ]. Thus, it is necessary to implement multidisciplinary management, including lifestyle modification, through early screening with awareness of MAFLD, which is a multifactorial disease in the current clinical field.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the incidence of newly diagnosed MAFLD increased. Bidirectionally, MAFLD is associated with COVID-19 severity [ 31 ]. Thus, it is necessary to implement multidisciplinary management, including lifestyle modification, through early screening with awareness of MAFLD, which is a multifactorial disease in the current clinical field.…”
Section: Discussionmentioning
confidence: 99%
“…13) During the coronavirus disease 2019 (COVID-19) outbreak, the proportion of newly diagnosed NAFLD cases was 25% among adults in a health checkup program in a Japanese study. 14) A Canadian study reported that the prevalence of MAFLD was 55.3% among participants with post-acute COVID-19 syndrome. 15) A c c e p t e d A r t i c l e Among children and adolescents, the global prevalence of NAFLD increased from 19.3 million in 1990 to 29.5 million in 2017, being higher in developed than developing regions.…”
Section: Epidemiologymentioning
confidence: 99%
“…A Japanese study examined 973 patients with health checks in 2018 and 2020. In this study, the absolute number of MAFLD patients increased from 261 to 305; however, as the authors identified predominantly higher alcohol consumption as a risk factor for this development, there is actually a definition problem of MAFLD in the strict sense[ 76 ]. Overall, these studies show a decrease in physical activity and an increase in weight in the general population.…”
Section: Influence Of Epidemic Hygienic Covid-19 Measures On Nafldmentioning
confidence: 99%